2015
DOI: 10.5578/mb.8881
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a New and Rapid Method, Brucella Coombs Gel Test With the Other Methods in the Serological Diagnosis of Brucellosis

Abstract: Diagnosis of brucellosis basically depends on blood and/or bone marrow culture and demonstration of high titer specific antibody or seroconversion in serum. In routine serological diagnosis of the disease, after screening with Rose Bengal test, the positive samples are studied with standart tube agglutination (STA) test with serial dilutions. However false negative results can be seen in STA test due to the existence of blocking antibodies, this test should be verified with Coombs anti-Brucella (CAB) or immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
2
10
0
1
Order By: Relevance
“…İrvem et al. reported that BCGT was an easy and rapid method for Brucella diagnosis, and found that test results of BICA and BCGT in their study were perfectly consistent . Sensitivity, specificity, negative predictive, and positive predictive values of BCGT were reported to be relatively high compared to other tests .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…İrvem et al. reported that BCGT was an easy and rapid method for Brucella diagnosis, and found that test results of BICA and BCGT in their study were perfectly consistent . Sensitivity, specificity, negative predictive, and positive predictive values of BCGT were reported to be relatively high compared to other tests .…”
Section: Discussionmentioning
confidence: 75%
“…ELISA systems are more costly and need more equipment . For true diagnosis, the combination of tests may be useful . In this article, we studied a new method, but only one study was conducted for BCGT method in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative methods, such as the enzyme-linked immunosorbent assay (ELISA) and AHG gel test, with which more samples in shorter time periods can be tested, are presented against standardization problems of agglutination tests with the possibility of different evaluations by different people in different laboratories, but evaluation of these tests is necessary before substitution (6)(7)(8)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Yüksek dilüsyonlu tüp aglütinasyon testi dışında; kültür, polimeraz zincir reaksiyonu (PCR), ELISA, roket immündifüzyon gibi alternatif serolojik testler problemi çözmede yardımcı olmaktadır (13,14). (10,15,16).…”
Section: Prozon Olayıunclassified